Mechanism of Apigenin against breast cancer stem cells: network pharmacology and experimental validation - Ou, Mengdie; Deng, Zhicheng; Shi, Yonghui; He, Jianxiong; Ye, Zicong; Guo, Ming; Cheng, Guohua; Wu, Junyan; Lv, Li (Frontiers in Pharmacology, 2024)
Apigenin (API), a traditionally sourced flavonoid, is recognized for its anti-neoplastic properties.Despite well-documented effects on tumorigenesis, the detailed therapeutic impact on breast cancer stem cells (BCSCs) and the associated molecular mechanisms are yet to be clarified. The objective of this study is to elucidate the therapeutic effects of API on BCSCs and to uncover its molecular mechanisms through network pharmacology and experimental validation. Interactions of API with candidate targets were examined through target screening, enrichment analysis, construction of protein-protein interaction networks, and molecular docking. MCF-7-derived BCSCs were utilized as a model system to investigate and substantiate the anti-BCSC effects of API and the underlying mechanism. Molecular docking studies have shown that API and TP53 exhibit favorable binding affinity. Compared with the negative control group, API effectively suppressed the expression of BCSC-related proteins such as ALDH1A1, NANOG, EpCAM, and MYC, down-regulated p-PI3K and p-AKT, and upregulated p53. This study demonstrates that API can play an anti-BCSC role by regulating the PI3K/AKT/p53 pathway in BCSCs of MCF-7 cells, highlighting its potential as a therapeutic agent for targeting BCSCs.